ANALISIS PERCAKAPAN NETIZEN PADA CHANNEL YOUTUBE @TotalPolitik SEBAGAI MEDIA RUANG PUBLIK KOMUNIKASI POLITIK - De Putri, Sekar; Toni, Ahmad (Jurusan Sosiologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Lampung, 2024)
Politics in Indonesia is currently in the public spotlight, especially ahead of the democratic party in 2024. The YouTube channel @TotalPolitik exists as a medium that consistently discusses the latest political issues through discussions with Indonesian political figures. The content uploaded on this channel is not only easily accessible to all groups, but also opens up discussion space through the comments column feature which allows netizens to express their views and opinions. This research aims to analyze how netizen conversations in the comments column of the YouTube Channel @TotalPolitik reflect the public's response to current political issues, especially in the era of the end of President Joko Widodo's term. By using a qualitative approach and online conversation analysis methods to understand interaction patterns, structures and communication dynamics that occur on digital platforms, this research finds that the YouTube Channel @TotalPolitik acts as a digital public space, where people can obtain information, express opinions and discuss openly about political communication. Analysis of netizen conversations in the comments column shows that there is a close relationship between topics in content and netizen conversation patterns, which creates public opinion about politics in Indonesia today. Several comments from the research results show criticism from the public towards the government in the Joko Widodo era which seemed to open up opportunities for political dynasties and nepotism.